2017
DOI: 10.1073/pnas.1705338114
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids promote Von Hippel Lindau degradation and Hif-1α stabilization

Abstract: Glucocorticoid (GC) and hypoxic transcriptional responses play a central role in tissue homeostasis and regulate the cellular response to stress and inflammation, highlighting the potential for cross-talk between these two signaling pathways. We present results from an unbiased in vivo chemical screen in zebrafish that identifies GCs as activators of hypoxia-inducible factors (HIFs) in the liver. GCs activated consensus hypoxia response element (HRE) reporters in a glucocorticoid receptor (GR)-dependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 53 publications
5
61
2
1
Order By: Relevance
“…Together, these data allow us to show the presence of a HIF-induced negative feedback, aimed to blunt steroidogenesis in order to regulate HIF activity itself. By the way, HIF-mediated negative feedback seems to be a logic homeostatic response aimed to avoid a further GCs-induced upregulation of HIF pathway, since hypoxia has been shown to trigger glucocorticoid response (Leonard et al, 2005) and consequently, cortisol was shown to increase HIF expression (Vettori et al, 2017).…”
Section: The Effect Of Hif Overexpression On Glucocorticoid Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Together, these data allow us to show the presence of a HIF-induced negative feedback, aimed to blunt steroidogenesis in order to regulate HIF activity itself. By the way, HIF-mediated negative feedback seems to be a logic homeostatic response aimed to avoid a further GCs-induced upregulation of HIF pathway, since hypoxia has been shown to trigger glucocorticoid response (Leonard et al, 2005) and consequently, cortisol was shown to increase HIF expression (Vettori et al, 2017).…”
Section: The Effect Of Hif Overexpression On Glucocorticoid Responsementioning
confidence: 99%
“…In our previous work, we identified new activators of the HIF pathway, e.g. betamethasone, a synthetic glucocorticoid drug (Vettori et al, 2017). Counterintuitively, GR loss of function was shown by Facchinello and colleagues to hamper the transcriptional activity linked to immune-response (i.e of cytokines Il1β, Il8 and Il6 and of the metalloproteinase Mmp-13) (Facchinello et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of the corticosteroid dexamethasone (Dex) affects macrophage phenotype by inhibiting the expression of genes related to inflammation and promoting genes related to homing, phagocytosis, and iron metabolism, functions that promote tissue regeneration. However, systemic Dex administration has failed in a number of clinical trials and cannot be tolerated by patients over long treatment regimens because of adverse side effects .…”
Section: Introductionmentioning
confidence: 99%
“…However, attempts to overcome chronic inflammation by locally administering anti-inflammatory macrophages into the damaged tissue have been unsuccessful because macrophages rapidly respond to their environment and quickly revert to a detrimental, inflammatory state. 9,10 Administration of the corticosteroid dexamethasone (Dex) affects macrophage phenotype by inhibiting the expression of genes related to inflammation [11][12][13] and promoting genes related to homing, 14 phagocytosis, [15][16][17][18][19][20] and iron metabolism, 21 functions that promote tissue regeneration. However, systemic Dex administration has failed in a number of clinical trials and cannot be tolerated by patients over long treatment regimens because of adverse side effects.…”
Section: Introductionmentioning
confidence: 99%